탄소강 배관 티에서의 유동가속부식으로 인한 감육 현상 규명 - 김경훈; Kyung Hoon Kim; 이상규; Sang Kyu Lee; 강덕원; Kang Deok Won (한국분무공학회지, 2011)
When pipe components made of carbon steel in nuclear, fossil, and industry plants are exposed to flowing fluid, wall thinning caused by FAC(flow accelerated corrosion) can be generated and eventually ruptured at the position of pressure boundary. The aim of this study is to identify the locations at which local wall thinning occurs and to determine the turbulence coefficient related to local wall thinning. Experiment and numerical analyses for the tee sections of down scaled piping components were performed and the results were compared. In particular, flow visualization experiment which was used alkali metallic salt was performed to find actual location of local wall thinning inside tee components. In order to determine the relationship between turbulence coefficients and local wall thinning, numerical analyses were performed for tee components in the main feedwater systems. The turbulence coefficients based on the numerical analyses were compared with the local wall thinning based on the measured data. From the comparison of the results, the vertical flow velocity component(Vr) flowing to the wall after separating in the wall due to the geometrical configuration and colliding with the wall directly at an angle of some degree was analogous to the configuration of local wall thinning.